Mini review: STING activation during non-alcoholic fatty liver disease - Li, Honggui; Guo, Xinlei; Aquino, Eduardo; Wu, Chaodong (Frontiers in Nutrition, 2023)
Non-alcoholic fatty liver disease (NAFLD) is one of the most common chronic diseases serving as a major threat to human health. While the pathogenesis of NAFLD is multi-factorial, inflammation is considered a critical factor driving the development and progression of NAFLD phenotype, including liver fibrosis. As an essential mediator of innate immunity, stimulator of interferon genes (STING) functions to promote anti-viral immunity. Accumulating evidence also indicates that STING functions to promote the proinflammatory activation of several types of liver cells, especially macrophages/Kupffer cells, in a manner independent of interferon production. Over the past several years, a significant body of literature has validated a detrimental role for STING in regulating the pathogenesis of hepatic steatosis and inflammation. In particular, the STING in macrophages/Kupffer cells has attracted much attention due to its importance in not only enhancing macrophage proinflammatory activation, but also generating macrophage-derived mediators to increase hepatocyte fat deposition and proinflammatory responses, and to activate hepatic stellate cell fibrogenic activation. Both intracellular and extracellular signals are participating in STING activation in macrophages, thereby critically contributing to NAFLD phenotype. This mini review summarizes recent advances on how STING is activated in macrophages in the context of NAFLD pathophysiology.